2019
DOI: 10.4103/ijpc.ijpc_110_19
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose oral ketamine as a procedural analgesia in pediatric cancer patients undergoing bone marrow aspirations at a resource-limited cancer hospital in India

Abstract: Aim:Many pediatric cancer patients undergo repeated bone marrow aspirations (BMAs) for diagnostic and treatment evaluation purposes. Full anesthesia is the standard of care during this procedure in high-income countries. At hospitals with low resources in low/middle-income countries many children undergo these painful procedures without sufficient pain relief. This study aimed to evaluate the usefulness of low-dose oral ketamine as a procedural analgesic in a low-resource pediatric cancer care department.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Although complication rates are low in bone biopsy/aspiration procedures, patients experience pain [ 34 ]. The literature shows that reported pain scores for BMAB range from 3.2 to 4 on a 10-point scale [ 2 , 6 ]. In their study, Jaddini et al(2016) reported that patients’ pain levels were high during the BMAB procedure [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although complication rates are low in bone biopsy/aspiration procedures, patients experience pain [ 34 ]. The literature shows that reported pain scores for BMAB range from 3.2 to 4 on a 10-point scale [ 2 , 6 ]. In their study, Jaddini et al(2016) reported that patients’ pain levels were high during the BMAB procedure [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yayla et al (2019) reported that 55–70% of the patients undergoing these procedures described BMAB as a painful process [ 5 ]. The literature states that pain scores reported for BMAB range from 3.2 to 4 on a 10-point scale [ 2 , 6 ]. At the same time, it was found that patients experience anxiety due to the pain experienced as a result of BMAB procedures [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies were conducted in a resource-limited hospital setting and, according to the results, oral ketamine could be defined as an option for lumbar puncture; bone marrow aspiration is defined as a painful and stressful procedure and oral ketamine is not sufficient. 47 , 48 …”
Section: Reviewmentioning
confidence: 99%